In Vitro Lipophilic Antioxidant Capacity, Antidiabetic and Antibacterial Activity of Citrus Fruits Extracts from Aceh, Indonesia - Ernawita, (Antioxidants (Basel), 2017)
This study reports in vitro lipophilic antioxidant, inhibition of α-amylase and antibacterial activities of extracts of peel and pulp of citrus samples from Aceh, Indonesia. HPLC (high-performance liquid chromatography), phytochemical, and FTIR (fourier transform infrared) analysis detected carotenoids, flavonoids, phenolic acids and terpenoids, contributing to the biological potencies. Most peel and pulp extracts contained lutein and lower concentrations of zeaxanthin, α-carotene, β-carotene and β-cryptoxanthin. The extracts also contained flavanone glycosides (hesperidin, naringin and neohesperidin), flavonol (quercetin) and polymethoxylated flavones (sinensetin, tangeretin). L-TEAC (lipophilic trolox equivalent antioxidant capacity) test determined for peel extracts higher antioxidant capacity compared to pulp extracts. All extracts presented α-amylase inhibitory activity, pulp extracts showing stronger inhibitory activity compared to peel extracts. All extracts inhibited the growth of both gram (+) and gram (−) bacteria, with peel and pulp extracts of makin showing the strongest inhibitory activity. Therefore, local citrus species from Aceh are potential sources of beneficial compounds with possible health preventive effects.